The present and the future of the RAS pathway: From function and genomics to inhibition. Issue 7 (2nd July 2016) - Gil-Bazo, Ignacio; Sweet-Cordero, Alejandro; Vicent, Silvestre
ABSTRACT: This meeting report summarizes the highlights of the II International Frontiers in Oncology meeting "The present and future of the RAS pathway: from function and genomics to inhibition" (RAS Frontiers) organized by the Center for Applied Medical Research (CIMA; Pamplona, SPAIN), the Clinic of the University of Navarra (CUN; Pamplona, SPAIN) and the Stanford Cancer Institute (SCI; Stanford University, CA, USA) in Pamplona (October 5–7, 2015). The RAS Frontiers meeting gathered together scientists from all over the world and featured the latest advances in the study of the RAS pathway covering aspects from basic research to translational and clinical investigation. Among the topics presented were novel mouse models that recapitulate human carcinogenesis and serve as preclinical platforms for drug testing, cutting-edge approaches for the identification of novel vulnerabilities and regulators of the RAS pathway, as well as current inhibitory strategies for the treatment of human RAS-driven cancers.